Affective Valence Regulates Associative Competition in Pavlovian Conditioning - Laurent, Vincent; Westbrook, R. Frederick; Balleine, Bernard W. (Frontiers in Behavioral Neuroscience, 2022)
Evidence suggests that, in Pavlovian conditioning, associations form between conditioned stimuli and multiple components of the unconditioned stimulus (US). It is common, for example, to regard USs as composed of sensory and affective components, the latter being either appetitive (e.g., food or water) or aversive (e.g., shock or illness) and, therefore, to suppose different USs of the same affective class activate a common affective system. Furthermore, evidence is growing for the suggestion that, in competitive learning situations, competition between predictive stimuli is primarily for association with the affective system activated by the US. Thus, a conditioned stimulus (CS) previously paired with one US will block conditioning to another CS when both are presented together and paired with a different US of the same affective class, a phenomenon called transreinforcer blocking. Importantly, similar effects have been reported when steps are taken to turn the pretrained CS into a conditioned inhibitor, which activates the opposing affective state to the excitor that it inhibits. Thus, an appetitive inhibitor can block conditioning to a second CS when they are presented together and paired with foot shock. Here we show that the same is true of an aversive inhibitor. In two experiments using rats, we found evidence that an aversive inhibitor blocked conditioning to a second CS when presented in compound and paired with food. Such findings demonstrate that affective processes and their opponency organize appetitive-aversive interactions and establish the valences on which they are based, consistent with incentive theories of Pavlovian conditioning.